The Account of the Illness and Death of Wladyslaw Vasa - Čiurinskas, Mintautas (Senoji Lietuvos literatūra, 2024)
The article presents an anonymous account of the last days of life and death of Wladislaw Vasa, King of Poland and Grand Duke of Lithuania, in Merkinė. The ruler died on 20 May 1648, and the text in question is one of the most detailed sources on this event. The article also includes extracts from Wladislaw Vasa’s will, hitherto unused in the historiography, which reflect his wish regarding the burial place and his bequest to St Casimir’s Chapel after his death. That this ruler’s heart rests in St Casimir’s Chapel of Vilnius Cathedral, which he had finished within his lifetime, was due to the circumstances of his death in Lithuania, the autopsy carried out, and the will of the nobles of Lithuania rather than that of the ruler. On the other hand, the latter was also exercised, by burying his body in the mausoleum of the Polish kings in Wawel Cathedral in Cracow. The introductory article discusses some of the circumstances of the ruler’s stay and illness in Merkinė, as well as the source itself. The publication includes a full Latin-Lithuanian translation of the account of Wladislaw Vasa’s illness and death.
Keywords: Wladyslaw IV Vasa; Merkinė; illness; disease treatment; ruler’s death